Beijing Digital Strong Motion Observation Network and analysis of the observational data - Rongshuai He; Jie Zhang; Fang Liang; Yongfu Bai; Qingcai Yu; Yunhui Cheng (地震科学进展, 2025)
This study introduces the development of the Beijing Digital Strong Motion Observation Network through the Ninth Five-Year Plan, Tenth Five-Year Plan, Olympic Guarantee, National Earthquake Intensity Rapid Reporting and Early Warning Project, and other projects, and counts the data recorded by the strong motion network from 2016 to 2022 and presents its application in the rapid output of seismic intensity measurements. It shows that the rapid output of the Beijing Digital Strong Motion Observation Network provides important reference values for earthquake emergency work in post-earthquake response, emergency disposal, command, and dispatch.